Pendampingan Usaha Mikro Kedai Mbak Ana Melalui Implementasi Pengembangan Produk dan Strategi Penetrasi Pasar (Lembaga Pengembangan Kinerja Dosen, 2025)
This research highlights the potential of Micro, Small and Medium Enterprises (MSMEs) in Sidoarjo, East Java, with a focus on Kedai Mbak Ana, in facing challenges during the COVID-19 pandemic. The data in this study, which is descriptive qualitative in nature, was obtained through an in-depth interview process, as well as a literature review. This research focuses on product innovation and market penetration strategies implemented by MSME players in the culinary sector. The findings show that measures such as developing menu variations and utilizing social media effectively increase the competitiveness of Kedai Mbak Ana. In conclusion, MSMEs that are able to adapt have a great opportunity to survive and thrive in the midst of crisis situations.